RIPK3 Contributes to Lyso-Gb3-Induced Podocyte Death - So-Young Kim; Samel Park; Seong-Woo Lee; Ji-Hye Lee; Eun Soo Lee; Miri Kim; Youngjo Kim; Jeong Suk Kang; Choon Hee Chung; Jong-Seok Moon; Eun Young Lee (Cells, 2021)
Fabry disease is a lysosomal storage disease with an X-linked heritage caused by absent or decreased activity of lysosomal enzymes named alpha-galactosidase A (α-gal A). Among the various manifestations of Fabry disease, Fabry nephropathy significantly affects patients’ morbidity and mortality. The cellular mechanisms of kidney damage have not been elusively described. Necroptosis is one of the programmed necrotic cell death pathways and is known to play many important roles in kidney injury. We investigated whether RIPK3, a protein phosphokinase with an important role in necroptosis, played a crucial role in the pathogenesis of Fabry nephropathy both in vitro and in vivo. The cell viability of podocytes decreased after lyso-Gb3 treatment in a dose-dependent manner, with increasing RIPK3 expression. Increased reactive oxygen species (ROS) generation after lyso-Gb3 treatment, which was alleviated by GSK’872 (a RIPK3 inhibitor), suggested a role of oxidative stress via a RIPK3-dependent pathway. Cytoskeleton rearrangement induced by lyso-Gb3 was normalized by the RIPK3 inhibitor. When mice were injected with lyso-Gb3, increased urine albuminuria, decreased podocyte counts in the glomeruli, and effaced foot processes were observed. Our results showed that lyso-Gb3 initiated albuminuria, a clinical manifestation of Fabry nephropathy, by podocyte loss and subsequent foot process effacement. These findings suggest a novel pathway in Fabry nephropathy.